Evaluation of acoustic changes in and the healing outcomes of rat eardrums with pars tensa and pars flaccida perforations. Issue 3 (22nd April 2022) - Liu, Yaoqian; Wu, Cuiping; Chen, Tingting; Shen, Qiyue; Xiong, Yuanping; Chen, Zhengnong; Li, Chunyan
Abstract: Objectives: To systematically explore the differences in acoustic changes and healing outcomes of tympanic membranes (TMs) with pars flaccida perforation (PFP) and pars tensa perforation (PTP). Methods: We created PFPs and PTPs of various sizes in Sprague–Dawley rats, and evaluated TM umbo velocity and hearing function using laser Doppler vibrometry and auditory brainstem response (ABR) measurement before and immediately after perforation. Two weeks later, hearing was reevaluated and TMs were investigated by immunohistochemical staining. Results: Small PFPs and PTPs did not significantly affect umbo velocity and hearing function. Large PFPs increased umbo velocity loss at low frequency (1.5 kHz) and elevated ABR thresholds within 1–2 kHz. Large PTP caused significant velocity loss at low frequencies from 1.5 to 3.5 kHz and threshold elevations at full frequencies (1–2 kHz). Two weeks after the perforation, the hearing function of rats with healed PFPs recovered completely. However, high‐frequency hearing loss (16–32 kHz) persisted in rats with healed PTPs. Morphological staining revealed that no increase in the thickness and obvious increase in collagen I level of regenerated par flaccida; regenerated pars tensa exhibited obvious increase in thickness and increased collagen I, while the collagen II regeneration was limited with discontinuous and disordered structure in regenerated pars tensa. Conclusion: The hearing loss caused by large PFP limits at low frequencies while large PTP can lead to hearing loss at wide range frequencies. PFP and PTP have different functional outcomes after spontaneous healing, which is determined by the discrepant structure reconstruction and collagen regeneration.